Hubungan Keterampilan Berpikir Kritis dan Kemampuan Pemecahan Masalah Siswa pada Materi Fluida Statis - Mandaliya Zahra; Nur Endah Susilowati; Duden Saepuzaman; Erni Ernawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking and problem-solving skills are two core competencies required in 21st-century physics learning, yet student learning outcomes in abstract topics such as static fluids remain relatively low. It is not yet known empirically to what extent critical thinking skills contribute to students' problem-solving abilities, so the relationship between the two needs further investigation. This study aims to analyze the correlation between critical thinking skills and problem-solving abilities of 11th-grade students on the topic of static fluids. A quantitative correlational approach was employed, involving 32 students in Bandung selected through purposive sampling. The instrument used was a two-tier test to measure both variables simultaneously while revealing the reasoning behind students' answers. Data were analyzed using Spearman correlation due to non-normal data distribution. The results showed a positive and significant but weak correlation (ρ = 0.335; p = 0.049), with critical thinking contributing only 11.2% to problem-solving ability. The remaining 88.8% was influenced by other factors such as conceptual mastery and mathematical ability. This finding indicates that critical thinking alone is insufficient to predict success in physics problem-solving. The implication is that instruction needs to be designed in an integrated manner, and further research is recommended to expand the sample and include additional predictor variables.